Translation Initiation Control of RNase E-Mediated Decay of Polycistronic gal mRNA - Jeon, Heung Jin; Kang, Changjo; N, Monford Paul Abishek; Lee, Yonho; Wang, Xun; Chattoraj, Dhruba K.; Lim, Heon M. (Frontiers in Molecular Biosciences, 2020)
In bacteria, mRNA decay is a major mechanism for regulating gene expression. In Escherichia coli, mRNA decay initiates with endonucleolytic cleavage by RNase E. Translating ribosomes impede RNase E cleavage, thus providing stability to mRNA. In transcripts containing multiple cistrons, translation of each cistron initiates separately. The effect of internal translation initiations on decay of polycistronic transcripts remains unknown, which we have investigated here using the four-cistron galETKM transcript. We find that RNase E cleaves a few nucleotides (14-36) upstream of the translation initiation site of each cistron, generating decay intermediates galTKM, galKM and galM mRNA with fewer but full cistrons. Blocking translation initiation reduced stability particularly of the mutated cistrons and when they were the 5’-most cistrons. This indicates that together with translation failure the location of the cistron is important for its elimination. The instability of the 5’ most cistron did not propagate to the downstream cistrons possibly due to translation initiation there. Cistron elimination from the 5’ end was not always sequential, indicating RNase E can also directly access a ribosome free internal cistron. The finding in gal operon of mRNA decay by cistron elimination appears common in E. coli and Salmonella.